Challenges Faced in Engaging American Indian Mothers in an Early Childhood Caries Preventive Trial - Tamanna Tiwari; Judith Albino; Terrence S. Batliner (International Journal of Dentistry)
Objective. This study explores the challenges faced by the research implementation team in engaging new mothers in a community oral health prevention intervention in an American Indian (AI) reservation community. Methods. Qualitative methods in the form of in-depth interviews were used in the study. Qualitative data were collected from research staff workers at a field site, who were involved in the implementation of a culturally tailored, randomized controlled trial of a behavioral intervention utilizing Motivational Interviewing (MI). Results. Several challenges were described by the field staff in engaging new mothers, including low priority placed on oral health, lack of knowledge, and distractions that reduced their ability to engage in learning about oral health of their child. Other difficulties faced in engaging the mothers and the AI community at large were distrust related to racial differences and physical and environmental barriers including poor road conditions, lack of transportation and communication, and remoteness of data collection sites. The field staff developed and applied many strategies, including conducting home visits, applying new communication strategies, and interacting with the community at various venues. Conclusion. Prevention interventions for ECC need to target AI mothers. Strategies developed by the field staff were successful for engaging mothers in the study.